A IMPORTÂNCIA DA COMPONENTE RELACIONAL NO ENSINO CLÍNICO DE ENFERMAGEM: A perspetiva dos estudantes de enfermagem - Pinto, José Manuel de Matos (2012)
The Relational Component in clinical teaching is a time to support orientation and transformation of doubts of students in relation to hospital patients. This contact with hospitalized patients consists of various aspects involving young students and disturb and leave them without adequate response to veiled communication of patients. Listening and processing of clinical situations allows new relational most fruitful paths. We did a qualitative study from the semi-structured with a satisfaction questionnaire where students describe the most important aspects in the relational component. We have categorized the findings through the methodology of Bardin. We conclude that students need support with a space where they can experience their dispersive anxieties and make use of concepts that enable it to deal with relational difficulties